The effect of letrozole treatment on the fertility and embryos parameters in female mice: Histological and hormonal study - Sally Adnan Mousa AL Rekabi; Noor Noori Abid Al Shemary (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate how letrozole affects reproductive hormones and embryos in mature female mice. Method: The investigative study was conducted from December 2021 to February 2022 at the Pathology Department of Kut Technical Institute, Al-Kut, Iraq, and comprised adult female albino mice weighing 23-25g. The mice were divided into control group A, those receiving 1.5mg/kg/day letrozole in group B, and those receiving 2.5mg/kg/day letrozole in group C. The intervention lasted 14 days. Blood samples were collected under anaesthesia by heart puncture for hormonal testing. Data was analysed using SPSS 15. Results: Of the 30 mice, 10(33.3%) were in each of the 3 groups. Right and left ovaries of mice in groups B and C showed a significant rise in multi-follicular cells compared to group A (p<0.05). Follicle-stimulating hormone, oestrogen and progesterone concentrations as well as luteinizing hormone increased significantly in the intervention groups compared to the control group (p<0.05). The impact of letrozole on embryos was significant in groups B and C compared to group A. Conclusions: Letrozole was found to have a positive effect on reproductive parameters and hormones in mice. Keywords: Mice, Ovary, Letrozole, oestrogen, Progesterone, Luteinizing hormone.